Development of mathematical pathways for VET students to articulate to related higher education courses : final report. - Beswick, Kim; Penesis, Irene; McNaught, Keith; Balatti, Jo; Roddick, John; Thomas, Giles; Callingham, Rosemary; Skalicky, Jane; Brown, Natalie; Fitzallen, Noleine; Leon de La Barra, Bernardo A.; Belward, Shaun; et al. (Office for Learning and Teaching, 2015)
Report from a project that developed an open educational resource (OER) to assist VET-qualified students to increase their mathematics skills and confidence in order to articulate to a related course in higher education. Four disciplines were examined: education, engineering, business and health science. The approach the project team took was to map the mathematics skills within the most commonly used VET qualifications that are used to transition into related higher education courses (e.g. the Diploma of Children's Services to the Bachelor of Education – Primary and the Diploma of Engineering – Technical to the Bachelor of Engineering). The gap in the mathematics knowledge was determined and resources were identified and/or developed to fill the gaps. All four pathways were trialled with students. (Executive summary, ed]